EMPOWERING B40 WOMEN ENTREPRENEURS IN SARAWAK THROUGH DIGITAL LITERACY: A SERVICE-LEARNING INITIATIVE - Suhaila, Saee; Noor Alamshah, Bolhassan; Rosita, Mohamed Othman; Abdul Rahman, Mat; Rosmawati, Bolhassan (UMK Press, 2025)
B40 women entrepreneurs practising Malay Traditional Medicine possess strong hands-on healing skills but remain digitally illiterate. Most of them lack essential digital competencies such as using a word processor to prepare and present professional reports and to promote their services and products through digital marketing. To bridge this gap, SULAM Faculty of Computer Science and IT, UNIMAS partnered with Koperasi Mamacare Sarawak Berhad to deliver a three-day “Bengkel Kemahiran Literasi Digital,” equipping 20 practitioners from all over Sarawak with the digital skills needed for certification and business growth. As a direct outcome, each participant successfully completed hands on assignments, submitting professional reports, presentation slides, marketing posters, and promotional videos, demonstrating their newly acquired competencies.